HUBUNGAN INDEKS MASSA TUBUH DENGAN TEKANAN DARAH TINGGI PADA LANSIA DI DESA RAWAPANJANG - Siti Jaliilah (2023)
Background: One of the causes of premature death is high blood pressure. Is, the biggest global disease in 2015, according to WHO. It is estimated that 1.56 billion people will suffer from high blood pressure by 2020. About 8 billion people globally and 1.5 million people in East-South Asia lose their lives due to high blood pressure every year. In the East-South Asia region, high blood pressure affects almost all adults. According to Riskesdas statistics for 2018, there are 21.8 percent of obese people in Indonesia. Since Riskesdas 2007, this figure has increased by 10.5 percent, and in Riskesda 2013 it has grown 14.8 percent. In addition, there was an increase in the prevalence of obesity by 13.6% in 2018. Research Objectives: To determine the relationship between body mass index and high blood pressure. Methods: This study uses a correlational descriptive quantitative research design with a cross sectional approach. With a sample of 92 elderly and with an error rate of 0.05. This research was carried out offline using a sphygmomanometer and screening sheet. Research Results: The results obtained for the highest body mass index values were in the isolated obesity category with a proportion of 47.8% and the highest blood pressure values were in the stage I high blood pressure category with a proportion of 77.2%. After the correlation test, it was found that there was no relationship between body mass index and high blood pressure, with p = 0.153 p (<0.05). The conclusion of this study resulted that there is no relationship between body mass index and high blood pressure which is not unidirectional.